The Ogre's Wife - Koertge, Ronald (Book collections on Project MUSE., 2013)
Ron Koertge wants to do nothing but delight. Armed with his trademark wit, he introduces readers to Little Red Riding Hood all grown up with a fondness for salsa and chips, explores the thorny relationship of Jackie Robinson and Pee Wee Reese, spies a Trojan pony and the children it bamboozles, and offers an alternate reading to the Icarus story. He meets Walt Whitman on the set of an X-rated movie, attends his gardener's funeral, and goes to his beloved race track. Seminal figures from pop mythology speak up in unexpected ways: The Beast, transformed by Beauty, hints that his new life isn't exactly what he expected. Gretel enrolls in night school, the ogre's wife from the beanstalk yarn writes a heart-rending story on her cutting board, and a group of fourth-graders on a field trip encounters Death. Occasionally setting aside free verse, there are couplets about a Bette Davis movie, a sestina about routine blood tests, a villanelle set in a topless bar, and a set of haibun that chronicles an entire day. Reverend Ike and John Lennon said, "Whatever gets you through the night." This book will do just that and carry you right on in to the next day, guaranteed.